Compliance Performance in Reporting on Zakat Institution in Indonesia - Hanum, Khuzaifah; Wibowo, Hendri Setiyo; Aziza, Syifa (Center of Strategic Studies (PUSKAS) BAZNAS, 2025)
The purpose of this study is to review the compliance performance in reporting on zakat institutions in Indonesia in 2023. Based on Laporan Pengelolaan Zakat Nasional 2023, the annual report of national zakat management published by BAZNAS RI, this paper constructs and analyses the implementation of compliance in reporting of zakat institutions in Indonesia. The study uses the content analysis method in developing the compliance performance frameworks and indicators in reporting referring to the zakat regulations in Indonesia. The result of review of this article formulated two main indicators of compliance in report: completing the reports and fulfilling the provisions in reporting. These findings are applicable to implement in evaluating the compliance performance in reporting on zakat institutions in Indonesia.